Meaning and Value of Learning Korean Language in the Graduate School - Valbuena Ancho, Inero (Thai Journal of East Asian Studies, 2019)
This qualitative study aims to determine how Filipino students view Korean language learning in the graduate school in terms of its meaning and value. The influence of Korean pop culture in the Philippines has created an impact on the number of Filipinos who become interested in learning Korean language and culture. Also, the Philippine’s Commission on Higher Education (CHED) through Memorandum Order 23, Series of 2010, has mandated the study of foreign languages in higher education to promote “understanding among nations”. Based on the gathered data, three themes emerged referring to the meaning of learning Korean language: self-discipline, cultural appreciation, and new learning. Also, the respondents see the value of the learning experience which was eventually clustered into two themes: realizing the world beyond the Philippines and professional growth. Overall, Filipino graduate students find learning Korean as a foreign language to be very meaningful and valuable. Findings of this study contribute to limited local literature in the Philippines concerning foreign language learning, particularly Korean language which is gradually gaining popularity in the country.